2020
DOI: 10.4269/ajtmh.20-0255
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Oxytocin Preparations in Malawi and Rwanda: Stabilizing Effect of Chlorobutanol

Abstract: Oxytocin is used for the prevention and treatment of postpartum hemorrhage, the leading cause of maternal mortality in low-and middle-income countries. Because of the high instability of oxytocin, most products are labeled for storage at 2-8°C. Some other products are on the market which are labeled for non-refrigerated storage, but independent evaluations of their stability hardly exist. In the present study, seven brands (nine batches) of oxytocin were purchased from wholesalers and medical stores in Malawi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…This study represents the first assessment of oxytocin and misoprostol quality in West Africa, showing results consistent with similar surveys conducted in Anglophone African countries [13,[18][19][20][21][22].…”
Section: Results Of Oxytocin and Misoprostol Products Sampled In Senegalsupporting
confidence: 88%
See 1 more Smart Citation
“…This study represents the first assessment of oxytocin and misoprostol quality in West Africa, showing results consistent with similar surveys conducted in Anglophone African countries [13,[18][19][20][21][22].…”
Section: Results Of Oxytocin and Misoprostol Products Sampled In Senegalsupporting
confidence: 88%
“…These findings align with other studies conducted LMICs assessing the quality of oxytocin and misoprostol, revealing instances of unregistered or unlicensed medicines. [13,[18][19][20]23] Typically, unregistered medicines are commonly discovered in private and informal sectors during such surveys. However, this study identified unregistered medicines in level-2 and level-3 of public health facilities in all regions evaluated, except in Abidjan in Côte d'Ivoire.…”
Section: Results Of Oxytocin and Misoprostol Products Sampled In Senegalmentioning
confidence: 99%
“…The package inserts of the preparations by Sterop (Belgium), Grindeks (Latvia) and Rotexmedica GmbH Arzneimittelwerk (Germany) stated the excipients, i.e. sodium chloride, different buffering agents, water for injection, and in case of the Sterop preparation also chlorobutanol, a preservative and stabilizing agent [ 40 ]. In contrast, no excipients were stated for the product by Jiangxi Xierkangtai.…”
Section: Resultsmentioning
confidence: 99%
“…Obviously, the use of oxytocin products which do not have to be stored in a refrigerator appears to be an attractive option, especially in LMICs. However, recent studies have shown that oxytocin products labeled for non-refrigerated storage may not have any better stability than products labeled for refrigerated storage, and on the contrary may even be less stable [ 40 , 44 ]. Therefore, international stakeholders including WHO have issued the recommendation “Buy quality oxytocin, keep it cool” and recommended that all oxytocin products should be stored at 2–8°C [ 16 , 48 ], irrespective of the manufacturer’s storage recommendation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, CB is known to undergo hydrolysis at elevated temperatures, forming hydrochloric acid and other acidic reaction products [9]. This is likely to explain the change in pH of preparations that contain CB, which has been observed at 40 • C. As expected, this effect was even more pronounced at 80 • C, with both preparations showing a pH of 2.0 in 5 days [10].…”
Section: Introductionmentioning
confidence: 70%